Changes in Serum Strongylus Vulgaris-Specific Antibody Concentrations in Response to Anthelmintic Treatment of Experimentally Infected Foals - Nielsen, Martin Krarup; Scare, Jessica; Gravatte, Holli Sullivan; Bellaw, Jennifer Lynn; Prado, Julio C.; Reinemeyer, Craig Robert (Frontiers in Veterinary Science, 2015)
Strongylus vulgaris is the most pathogenic nematode parasite of horses. Its extensive migration in the mesenteric blood vessels can lead to life-threatening intestinal infarctions. Recent work has shown that this parasite is still identified among managed horse populations. A serum enzyme-linked immunosorbent assay (ELISA) has been developed for the detection of migrating larvae of S. vulgaris. Previous work has documented an increase in ELISA values following larvicidal treatment with ivermectin and suggested that the target parasite antigen is primarily produced by the later larval stages. The aim of this study was to experimentally inoculate cohorts of foals with S. vulgaris, and then compare ELISA responses to early or later ivermectin treatments. Fifteen foals were held in confinement and infected orally with ~ 25 S. vulgaris third-stage larvae on days 0, 7, 14, and 21. Foals were weaned on Day 43 and turned out to a pasture not previously grazed by horses. Foals remained at pasture continuously until the study was terminated on Day 196. On Day 55, foals were randomly allocated to three treatment groups of five each. Group 1 received ivermectin on Day 56, Group 2 received ivermectin on Day 112, and Group 3 foals served as untreated controls. Serum and fecal samples were collected at 28-day intervals throughout the study. Serum samples were analyzed with the S. vulgaris-specific ELISA and fecal samples were processed for fecal egg counting. The ELISA values of Group 1 foals were significantly lower than Groups 2 or 3 on days 140-196. Both treated groups exhibited increased ELISA values following ivermectin treatment. Results indicate that the target diagnostic antigen is produced throughout the course of arterial infection with S. vulgaris, but that an early ivermectin treatment can reduce the cumulative antigen produced over the course of an infection.